Neocatechumenal Way. An Example of Controlled Innovation in Catholic Church - Šantek, Goran-Pavel (2003)
The paper focuses on the Neocathecumenal Way, an ecclesiastical movement that arose in 1964, with the purpose of reintegration of the disintegrated symbols of the Spanish Catholics’ sacred self. The main critical issues to be considered will be the process of routinization and formalization by which a charismatic movement becomes a recognized and structured part of the Catholic Church, religion as a means for the transformation of identity, and the Croatian specificities of this global movement.